Steroid-sparing effect of ciclosporin A 1 mg/mL: 5-year case series of 107 children and young people with vernal keratoconjunctivitis. Issue 1 (15th December 2022) - Dahlmann-Noor, Annegret Hella; Roberts, Clare; Muthusamy, Kirithika; Calder, Virginia; Hingorani, Melanie
Abstract : Background/aims: To explore the steroid-sparing and other therapeutic effects of ciclosporin A (CsA) 1 mg/mL in the management of vernal keratoconjunctivitis (VKC). Methods: Open retrospective single-group interventional consecutive cohort study (case series) of 107 children and young people (CYP) age 4.4–18 years with severe and/or recurrent VKC who were prescribed CsA 1 mg/mL between November 2015 and May 2021 at one institution. Review of electronic patient records, noting clinical indication for prescribing CsA 1 mg/mL, dosage prescribed at initiation and follow-up, impact on steroid usage before and after commencing CsA as well as adverse events and indications for discontinuation of treatment. Results: The median number of inflammatory episodes requiring treatment with topical corticosteroids fell from 3 (IQR 2–4) during the 12 months prior to CsA 1 mg/mL to 1 (IQR 0–3) during the 12 months after, excluding steroid prescriptions with the first CsA 1 mg/mL prescription (Wilcoxon signed ranks test, two tailed, p<0.01). In the 12-month period following initiation of CsA 1 mg/mL with concomitant prescription of topical corticosteroids (n=82), daily dosage of steroids was reduced in 79 (96.3%) and discontinued in 67 (81.7%). The median number of hospital clinic visits fell from 4 (IQR 3–5) to 3 (IQR 2–5) (Wilcoxon p<0.01). Adverse events leading to discontinuation of CsA 1 mg/mL within 12 months of starting included stinging (instillation site pain) (6/107, 5.6%) and skinrash (1/107, 0.9%). Conclusion: Commercial preparations of CsA 1 mg/mL, licensed for severe VKC in CYP, significantly reduce the need for concomitant topical corticosteroids and hospital clinic visits. Adverse events which may lead to discontinuation are stinging and skin rash.